Transforming Student Data Governance through a Web-Based Management Information System (MIS): A Systematic Literature Review - Sep Arinda Risa Kamal; Desi Rahmawati; Siti Zulaikha; Syafaat Ariful Huda (FKIP - Universitas Riau, 2026)
In the era of Industrial Revolution 4.0 and Society 5.0, educational data governance demands speed, accuracy, and real-time accessibility. Manual student data management often leads to redundancy, inefficiency, and delays in strategic decision-making. This study aims to analyze the effectiveness and impact of transforming student data governance through the implementation of Web-based Management Information Systems (MIS). The research method employs a Systematic Literature Review (SLR) using the PRISMA protocol on 32 reputable scientific articles (Scopus and SINTA 1-2) published between 2015 and 2025. The synthesis analysis shows that the transformation to web-based MIS has a significant impact on four main dimensions: (1) Operational efficiency of school administration through automation; (2) Improvement of data validity and integration (interoperability); (3) Support for data-driven decision making for school principals; and (4) Improvement of public services to parents. However, challenges related to cybersecurity and human resource (HR) readiness remain major obstacles. These findings confirm that the digitalization of data governance is not just a change of tools, but an organizational cultural transformation towards an accountable and futuristic school.